Eficiência fotossintética da cana-de-açúcar submetida à aplicação de atrazine e tebuthiuron em pré-emergência - Girotto, Marcelo (2011)
The objective of this work was to assess the photosynthetic efficiency of sugarcane crop, in pre-emergency application, of two inhibiting photosynthesis herbicides. For sugar cane cuttings planting (SP80-3280 genotype), pots with a capacity of 8 dm3 were used. Atrazine and tebuthiuron application was performed by using a stationary spray installed in laboratory conditions and after treatment application, plants were transported to a green house where were kept until the end of the trial. The reading of electrons transport rate (ETR) was conducted in the middle portion of the youngest leaves of sugarcane with a portable fluorometer, with intervals for ETR assessment constituted by: 16, 17, 19, 25 and 30 days after herbicide application. It was also developed visual analysis of phytotoxiciy performed 30 days after application. The results showed that tebuthiuron herbicide caused greater reduction in electrons transport rate than atrazine. In relation to herbicide symptoms, there was no significant difference between the studied herbicides. At the end of the study it could be verified that the chosen methodology by using fluorometer to measure the electrons transport rate after herbicide application was adequate, allowing verifying sugar cane crop intoxication, even before any visual detection of herbicides performance in plants.